PENGEMBANGAN HANDOUT DIGITAL TOPIK KEANEKARAGAMAN HAYATI BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) SISWA KELAS X SMA NEGERI 1 METRO - Yosi Melinda; HRA Mulyani; Muhfahroyin (EDUBIOLOCK, 2025)
The purpose of this research is to produce a product in the form of Digital Handout of biodiversity material that is valid and easy to understand by students and educate students to maintain biodiversity. This research is development in nature using the ADDIE development method which consists of five stages, namely 1) Analysis, in this stage the main activity is to analyze the need for the development of teaching materials in learning objectives. 2) Design, the design stage includes several learning media development plans. 3) Development, at this stage the development of Handout is carried out in accordance with the design that has been made. 4) Implementation, at this fourth stage a real test is carried out limited to the School, with a small group test of 15 students from a total of 36 students taken randomly. 5) Evaluations, Evaluation is the process of giving value to the development of learning materials. The results of the assessment are used to provide feedback on the development of teaching materials. The products that have been developed have been validated by design experts and material experts, the results obtained from material experts are 94% with "very feasible" criteria, design experts are 96% with "very feasible" criteria. And the results of the trial to students amounted to 93% with the criteria "Very feasible".